Participant Observation to Apply an Empirical Method of Codesign with Children. (9th July 2022) - Romero-Ternero, M. C.; García-Robles, R.; Cagigas-Muñiz, D.; Rivera-Romero, O.; Romero-Ternero, M. J.
Abstract : Dental anxiety in children is a well-documented problem in the scientific literature. Tools mediated by Information Technology have been shown to positively influence children's mood based on distraction as well as relaxing activities. We propose an empirical method of codesign with children to generate app content for reducing dental anxiety. The results are embedded in text through a thick description as an ethnographic technique. The method was applied to 163 children (6–8 years old) from a summer school and a primary school, obtaining multimedia products that were integrated into an app prototype. Finally, although this use case of the presented method is applied to the health field, it can be transferred to any other field of application of codesign to children by using material that is specific to new scenarios.